Tinjauan Quran Surat An Nahl: 125 dalam Penerapan Metode Pendidikan - Ahmada, Futiha Alambarra Amaan; Fauzi, Sriyono (TSAQOFAH, 2024)
In an effort to achieve educational goals, the use of methods or ways of educators in delivering learning is very necessary. Al-Qu'ran which is a guide to human life has mentioned many educational methods in its content. This research aims to reveal what educational methods are found in the Qur'an, especially QS. An-Nahl verse 125 along with its relevance to education. To answer this problem, researchers use qualitative research methods with the type of literature study that produces findings in the form of descriptive explanations based on written sources. From the analysis, it is found that in QS. An-Nahl: 125 there are 3 educational methods that are relevant to the concept of education. The first, bi al-hikmah method is a method of conveying knowledge wisely and in the form of exemplary in order to create a practice from the understanding of students. Second, the mau'idzah hasanah method is a method of giving advice in the form of both recommendations and prohibitions carried out with gentleness and compassion in order to instill values and norms in the personalities of students. The third, mujadalah method or discussion method carried out in order to explore the potential of students to explore knowledge and express opinions that are in accordance with truth and science.